Demokratičnost demokracije in alternative? - Dragoš, Srečo (Teorija in praksa, 2011)
Questions related to the democratic system and its alternatives are as relevant today as they were before the Second World War. The attitude of the major pre-war competitive political blocs in the Slovenian territory towards democracy remained virtually unchanged: it was pragmatic, instrumentalised and reserved. In the plethora of pre-war corporate models of social regulation three models are particularly advanced: Gosar's model, Jeraj's model and the model of The Slovenian Workers Federation. The comparison of these three models yields conclusions, which carry important implications for the current issues related to the question mentioned in the title. In the final section of the article, the conclusions (constructs) are divided into four types, which can be expressed as combinations of political problems and solutions typical of the Slovenian past and present times.
Keywords: Catholicism; Katolicizem; Cerkev; Church; Corporativism; Korporativizem; Democracy; Demokracija; Samoupravljanje; Self-management; Social state; Socialna država; welfare state; Socialna politika; Social policy